2013
DOI: 10.3922/j.psns.2013.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control and the adolescent brain: A review of fMRI research.

Abstract: Adolescence is a developmental period frequently characterized by impulsive behavior and suboptimal decision making, aspects that often result in increased rates of substance abuse, unprotected sex, and several other harmful behaviors. Functional magnetic resonance imaging (fMRI) studies have attempted to reveal the brain mechanisms that underlie the typical inhibitory control limitations associated with this developmental period. In the present review, all available studies in the PsycINFO, PubMed, and Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The ACC is closely related to the SMA. Highly involved in error monitoring and detection, the ACC has been found to show less activity during correct trials and more activity during error trials [38] , [39] , thus ACC was implicated to signal to the prefrontal cortex to bias against incorrect selection when an erroneous language was chosen. Luk et al suggested that the SMA related structures may sometimes combine with the dorsal ACC to form a region known as the Rostral Cingulate Zone [40] , [41] in performing demanding tasks in terms of response control, performance monitoring and error detection [42] , [43] and it is the superior part of the Rostral Cingulate Zone that is consistently activated in language switching [10] .…”
Section: Discussionmentioning
confidence: 99%
“…The ACC is closely related to the SMA. Highly involved in error monitoring and detection, the ACC has been found to show less activity during correct trials and more activity during error trials [38] , [39] , thus ACC was implicated to signal to the prefrontal cortex to bias against incorrect selection when an erroneous language was chosen. Luk et al suggested that the SMA related structures may sometimes combine with the dorsal ACC to form a region known as the Rostral Cingulate Zone [40] , [41] in performing demanding tasks in terms of response control, performance monitoring and error detection [42] , [43] and it is the superior part of the Rostral Cingulate Zone that is consistently activated in language switching [10] .…”
Section: Discussionmentioning
confidence: 99%
“…The IFG, a region implicated in cognitive control and selection of competitive information and inhibition (Liakakis et al, 2011), was another area repeatedly found to be negatively associated to the consumption of screen-based devices. At the same time, the IPL (part of the DMN), which is related to different aspects of bottom-up attention (Igelström and Graziano, 2017), the OFC, which is involved in the different phases of the decision-making process including the (internal) representation of rewards (Kringelbach and Rolls, 2004;Kringelbach, 2005), and the ACC, which is a central region for cognitive control in general (Jaeger, 2013), have been constantly reported as less connected or developed in heavy adolescent media users. These areas are all involved in the implementation of goal-directed behaviors, which demand to control impulses and delay gratifications to optimize outcomes.…”
Section: Globus Pallidus (Gp)mentioning
confidence: 99%
“…In general, personality-based impulsivity traits increase with the onset of puberty through the early 20s and then level off in the transition into middle-adulthood Romer & Hennessy, 2007;Steinberg et al, 2008), although this pattern is not as robust for sensation seeking (Collado et al, 2014;Harden & Tucker-Drob, 2011;Pedersen et al, 2012). For behavioral measures, delayed reward discounting decreases from adolescence into adulthood (Green et al, 1994;Olson et al, 2007;Prencipe et al, 2011) and response inhibition performance improves from adolescence into adulthood (Jaeger, 2013;López-Caneda et al, 2014). It has been suggested that the increase in impulsivity during adolescence results from the gap between the early development in the affective processing system (including areas of the mesolimbic dopamine circuit) and later development of the cognitive control system (including the lateral prefrontal cortex and parts of the anterior cingulate cortex) (Ernst and Fudge, 2009;Somerville et al, 2010;Stautz and Cooper, 2013;Steinberg, 2008).…”
Section: Developmental Changes In Impulsivity Across the Lifespanmentioning
confidence: 99%